Comparative characteristics of morphometric, biometric and biomechanical parameters of myopic eyes in children with different types of progressive myopia - T. E. Tsybulskaya (Zaporožskij Medicinskij Žurnal)
Aim. With the progression of myopic process in children the changes of morphometric, biometric and biomechanical parameters of eyeball are observed. In order to study these parameters in the axial and refractive myopia 32 patients (64 eyes) with axial and 26 patients (46 eyes) with refractive myopia have been examined.